The Role of Oxidative Stress in Breast Cancer Pathogenesis and Progression - Bashir Ahmad Karimi; Abdulrahim Shariati (Penerbit Hellow Pustaka, 2025)
Breast cancer is one of the most common and deadly cancers in women, and numerous studies have sought to identify the molecular and cellular factors involved in its onset and progression. Oxidative stress, defined as an imbalance between the production of reactive oxygen species (ROS) and antioxidant systems, plays a pivotal role in the pathogenesis of many chronic diseases, including cancer. This article examines the effects of oxidative stress in breast cancer and analyzes its relationship with genetic damage, as well as protein and lipid alterations, and metastatic processes. ROS can inflict significant damage on cellular structures through the oxidation of DNA, proteins, and lipids, leading to genetic mutations, chromosomal instability, and disruptions in essential cellular processes such as cell proliferation and programmed cell death (apoptosis). In addition to its role in cancer initiation, oxidative stress contributes to cancer progression and metastasis. Considering the complex role of oxidative stress in breast cancer, this article proposes therapeutic strategies focused on managing oxidative stress and introduces new approaches to improve current breast cancer treatments.